Five-phase space vector modulation voltage source inverter using large, medium and zero vector combination technique: article / Naqiuddin Razalini - Razalini, Naqiuddin (Universiti Teknologi MARA (UiTM), 2014)
The development of power electronics toward the future is massive and leads to the application of electric drives with the number of phase greater than three such as the multi phase inverter. This research is about to generate five-phase AC voltage waveform from the five-phase space vector modulation VSI using the combination of active (large and medium) vector with zero vector switching technique and analyzed its result by implementing the switching technique into the simulation and hardware and record the performance of the output at the load. The Low Order Harmonic (LOH) such as 3 ,Sib and 71b harmonic produce by d3-q3 subspace will be reduce by using the combination of large, medium and zero vector technique